Determination of Iron: Electrochemical Methods - Lu, M; Rees, N; Kabakaev, A; Compton, R (2012)
Iron is an abundant element in the environment which plays an important role in environmental and biological systems. In particular, its essential function in photosynthesis has been seen as a limiting factor for phytoplanktons in ocean waters. Thus, sensitive speciation and determination of iron is of major interest, and many techniques have been established for analytical purposes. Electrochemical methods have been commonly explored due to their inexpensive, simple and rapid nature, with adsorptive stripping voltammetry (AdSV) being widely used due to its ability to complex and preconcentrate iron ions for ultrasensitive detection. This paper aims to present a review of recent determinations of trace iron using electrochemical methods. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.